OPTIMALISASI KINERJA PEGAWAI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KANTOR URUSAN AGAMA KECAMATAN BINAKAL KABUPATEN BONDOWOSO - Turmudi, Imam (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
Service is a process of directly fulfilling the needs of activities carried out to meet the needs of the community so as to obtain satisfaction. To get good service results, the role of employees is very important to serve the needs of the community. Religious Affairs Office employees have tried their best with existing capabilities and facilities to provide the best service to the community. However, the duties and roles of the Religious Affairs Office in Binakal District have not been realized properly due to a lack of staff to carry out the planned objectives and inadequate facilities so that service is still not optimal. The method used in this thesis is a qualitative method. This qualitative research uses a field research approach. By using data collection techniques carried out by means of observation, interviews and documentation, and also using data triangulation in testing the validity of the data obtained. The results of this research are: First, the form of public service at the Binakal Subdistrict Religious Affairs Office serves the community's religious needs, including: the field of religious affairs (marriage and reconciliation), the field of data management and KUA management information, the field of the Sakinah family, the field of mosques and the field of development, the field of development. Sharia, Waqf Sector, Zakat Sector, Hajj and Umrah Sector, Halal Products Sector, Social Worship Sector Apart from that, there are KUA instructors who are implementers of religious advice guidance. Second, the supporting factors at the Religious Affairs Office, Binakal District, Bondowoso Regency, namely the level of education, online system services and the availability of a complete service system. Meanwhile, the inhibiting factors are: Lack of employee discipline and responsibility for their work, lack of employee ability to use technology and lack of public understanding of the implementation of online systems